Influenza vaccine effectiveness against laboratory confirmed influenza in Greece during the 2013–2014 season: A test-negative study. Issue 2 (3rd January 2015) - Lytras, Theodore; Kossyvakis, Athanasios; Melidou, Angeliki; Exindari, Maria; Gioula, Georgia; Pogka, Vasiliki; Malisiovas, Nikolaos; Mentis, Andreas
Highlights We assessed influenza vaccine effectiveness in Greece for the 2013–2014 season. The study employed the test-negative design. We found moderate effectiveness against H1N1pdm09 and low against H3N2. Vaccine coverage in Greece was very low, even among people aged 60 and over. Vaccine effectiveness studies should be taken note of for vaccine strain selection.